657P Cipaglucosidase alfa + miglustat in late-onset Pompe disease: two non-ambulatory patients switching from high-dose, high-frequency alglucosidase alfa - Byrne, B.; Castelli, J.; Jain, V.; Sitaraman Das, S.; Zhang, J. (Neuromuscular disorders : NMD, 2024)
Late-onset Pompe disease (LOPD) is a rare, heterogeneous disorder characterised by progressive loss of muscle and respiratory function. An open-label, Phase I/II study (ATB200-02; NCT02675465) evaluated the safety and long-term efficacy of cipaglucosidase alfa plus miglustat (cipa+mig; a two-component therapy for LOPD). As data are limited in non-ambulatory patients or those switching from high-dose, high-frequency (40 mg/kg every week) alglucosidase alfa (alg) to cipa+mig, we analysed outcomes in two non-ambulatory participants of ATB200-02 aged 18–25 years (Patient 1, female; Patient 2, male). Both received alg for >7 years (including >2 years on high dose, high frequency) before entering ATB200-02 and switching to cipa+mig (20 mg/kg + 260 mg every 2 weeks). Outcomes up to 78 months (mos) post-baseline (BL) were available. In both patients, upper body quantitative muscle test scores showed marked increases from BL over the first 12 mos, with further improvements up to 54 mos (Patients 1 and 2: 42.5 and 17.7 kg at 54 mos, vs 7.7 and 0 kg at BL). Subject and Physician Global Impression of Change scores were improved at 6 mos and maintained throughout follow-up. The severity of fatigue was above BL at 6 mos, but then improved vs BL at all assessments at 12–72 mos. Rotterdam Handicap Scale scores fluctuated over time, with broad similarity vs BL at 36–78 mos in Patient 1, and initial improvement vs BL followed by a decline at 54–72 mos in Patient 2. In both patients, levels of disease biomarkers urine hexose tetrasaccharide and serum creatine kinase were decreased vs BL at every post-BL assessment. Eleven non-serious adverse events were reported in the two patients; none were infusion-associated reactions. These two non-ambulatory adults living with LOPD showed sustained, long-term benefits in multiple outcomes, providing evidence for clinicians considering a transition from high-dose, high-frequency alg to cipa+mig. Supported by Amicus Therapeutics, Inc.